Laquinimod Inhibits Inflammation-Induced Angiogenesis in the Cornea - Li, Zuohong; Chen, Jianping; Lei, Lei; Jiang, Nan; Zhu, Yanling; Jia, Yu; Zhuo, Yehong; Su, Wenru (Frontiers in Medicine, 2020)
Background: Inflammation-induced angiogenesis plays a critical role in many eye diseases, and abnormal angiogenesis inhibition is regarded as a therapeutic approach. Here, we examined the effects of laquinimod on inflammatory corneal angiogenesis. Methods: Mouse model of corneal neovascularization was induced by NaOH. Laquinimod or control vehicle were topically applied to alkali-treated eyes twice a day for 10 days. Corneal neovascularization, infiltrating inflammatory cells, and the levels of chemokines, proinflammatory cytokines were assessed. RAW cells and human umbilical vein endothelial cells were used in vitro to further explore the underlying mechanisms of the effects of laquinimod on inflammation-induced angiogenesis. Results: Topical administration of laquinimod to the injured corneas dramatically inhibited alkali-induced corneal neovascularization and decreased inflammatory cell (such as macrophage) infiltration in a corneal injury mouse model. Laquinimod significantly downregulated the expression of chemokines (monocyte chemotactic protein-1 and macrophage inflammatory protein-1), proinflammatory cytokines (interleukin-1β and tumor necrosis factor-alpha), vascular endothelial growth factor, nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing 3 and apoptosis-associated speck-like protein containing C-terminal caspase-recruitment domain adaptor protein in both injured corneas and RAW cells. In vitro, laquinimod also dramatically inhibited the proliferation, migration and tube formation of human umbilical vein endothelial cells. Conclusion: Laquinimod inhibits inflammation-induced angiogenesis in the cornea. These results suggest that laquinimod is a potential new therapeutic option for corneal neovascularization and other angiogenesis-associated diseases.